Links between use of the secure base script and preschool children’s knowledge about emotions - Fernandes, Carla (2019)
The links between attachment security and multiple aspects of emotional development have been studied for several decades. Although these studies are valuable insofar some answers related to representations of attachment and emotion knowledge are still open. Preschool aged children (N=40) participated in this study. We used the Attachment Story Completion Task as their attachment measure, with representations measured as access to and use of the Secure Base Script (SBS) to organize children’s attachment relevant narratives. Emotional knowledge was assessed using the Affect Knowledge Test. Our main goal was to demonstrate that the SBS behaves like a typical measure of attachment representations with respect to its relations with children’s emotion understanding. Results suggested that children with secure attachment histories tend to have a larger fund of emotion knowledge. The SBS measure behaved similarly to other measures of attachment security suggesting its validity as a measure of attachment representations during early childhood.